Factors influencing adherence among older people with osteoarthritis. Issue 9 (September 2016) - Loew, Laurianne; Brosseau, Lucie; Kenny, Glen; Durand-Bush, Natalie; Poitras, Stéphane; Angelis, Gino; Wells, George
Abstract This study aims to identify potential factors that could affect adherence and influence the implementation of an evidence-based structured walking program, among older adults diagnosed with knee osteoarthritis. A total of 69 participants with mild to moderate osteoarthritis of the knee fulfilled an online survey on potential factors that could affect their adherence to an evidence-based structured walking program. Adherence with regard to the influencing factors was explored using a logistic regression model. Results tend to show higher odds of adhering to the evidence-based walking program if the participants were supervised (more than 2.9 times as high), supported by family/friends (more than 3.7 times as high), and not influenced by emotional involvement (more than 11 times as high). The odds of adhering were 3.6 times lower for participants who indicated a change in their medication intake and 3.1 times lower for individuals who considered themselves as less physically active (95 % confidence interval (CI)). Our exploratory findings identified and defined potential adherence factors that could guide health professionals in their practice to better identify positive influences and obstacles to treatment adherence, which would lead to the adoption of a more patient-centered approach. A large-scale study is required to clearly delineate the key factors that would influence adherence. We addressed a new knowledge gap by identifying the main strategies to promote the long-term adherence of community-based walking program.